Heat transfer augmentation of Al2O3-Cu/water hybrid nanofluid in circular duct with inserts. Issue 1 (31st December 2022) - Wollele, Muluken Biadgelegn; H.V, Harish; Assaye, Mebratu
Abstract: Nanotechnology has opened up new avenues for industrial efficiency and performance. The Al2 O3 -Cu/water hybrid nanofluid with and without insert is analyzed numerically and validated to show heat transfer enhancement. A circular duct with inserts, a tube length of 3 m, a hydraulic diameter of 0.01 m, tube wall with a constant heat flux of 20 kW/m 2, and a twist ratio of 125 were used to examine Al2 O3 -Cu/water hybrid nanofluid in turbulent regime. At Re = 20, 000, due to insertion of twisted tape, there is an additional mixing of fluid that takes place, leading towards increase in temperature of around 1–1.75% when compared with that of without inserts. The Nusselt number is improved for plain twisted tape tube by 1.5–2.0% higher than plain tube as revealed in the result. Moreover, there is a 1.01 times improvement in performance evaluation criteria when twisted tape is inserted instead of plain tube.